2009
DOI: 10.1007/s12522-009-0044-7
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant follicle‐stimulating hormone (follitropin alfa) for ovulation induction in Japanese patients with anti‐estrogen‐ineffective oligo‐ or anovulatory infertility: results of a phase II dose–response study

Abstract: A starting dose of 75 IU r-hFSH was associated with a favorable efficacy and safety profile for OI in Japanese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The results confirmed that maintaining the same FSH starting dose for 14 days before increasing it in a step-up regimen is critical to control the risk of over-response [20]. A randomized, double-blind, dose-finding study aiming to determine the optimal regimen of r-hFSH for OI in Japanese women with amenorrhea or anovulatory infertility concluded that a starting dose of 75 IU of r-hFSH (compared to a starting dose of 37.5 IU and 150 IU) is associated with favorable results and safety profile [21].…”
Section: Global Journal Of Reproductive Medicinementioning
confidence: 99%
“…The results confirmed that maintaining the same FSH starting dose for 14 days before increasing it in a step-up regimen is critical to control the risk of over-response [20]. A randomized, double-blind, dose-finding study aiming to determine the optimal regimen of r-hFSH for OI in Japanese women with amenorrhea or anovulatory infertility concluded that a starting dose of 75 IU of r-hFSH (compared to a starting dose of 37.5 IU and 150 IU) is associated with favorable results and safety profile [21].…”
Section: Global Journal Of Reproductive Medicinementioning
confidence: 99%
“…An earlier Phase II dose-finding study using a low-dose step-up protocol for OI showed that a starting dose of 75 IU r-hFSH (follitropin alfa), with 37.5 IU increments, was associated with a favorable efficacy and safety profile in Japanese women with amenorrhea I or anovulatory infertility [10]. In this Phase III study, the efficacy and safety of follitropin alfa were compared with those of purified urinederived FSH (urofollitropin), using a low-dose step-up protocol for follicle development and OI in Japanese women with anovulatory infertility who were menstruating or had progestin-positive amenorrhea, including PCOS.…”
Section: Introductionmentioning
confidence: 99%